Communicating risks : factors influencing Filipinos living in high-risk areas to follow pre-emptive evacuation procedures - BALUNDAY, JIMWEL (Archīum Ateneo, 2017)
With recent mega disasters, risk communication has become one of the important areas in disaster risk reduction. Pre-emptive evacuation has been a practice in the Philippines to lessen the number of casualties. Risk perception as part of the risk communication process was explored using the three predictors of the Theory of Planned Behavior. The researcher surveyed 1,200 respondents from the provinces of Aurora, Eastern Samar, and Davao Oriental of the Philippines regarding factors that influenced the participants to follow pre-emptive evacuation orders. This study explored factors that include attitude towards being safe, secured and comfortable, and acceptability of being called an evacuee; societal factors that include local officials, friends, experts, television and radio; and perceived control that includes difficulty and confidence in following evacuation and influences from government, family and faith. The researcher explored the significance of socio-demographic and economic variables such as age, sex, civil status, income, education, home ownership, living arrangement, awareness and knowledge on the proximity of the evacuation center. The researcher also investigated the effectiveness of NDRRMCs communication process in giving evacuation orders. Results were scored based on the recommendation of Francis and colleagues (2004), statistical models such as factor analysis, data reliability test, and Ordinary Least Squares (OLS) were used to examine the validity and relationships of factors. Overall, socio-demographic and economic determinants were significant in following pre-emptive evacuation procedures, with subjective Norms having the strongest positive impact on the desired behavior. The respondents experienced the highest social pressure to the local officials; however, level of importance of external referent differs across all the provinces. The aggregated results showed strongest relationship of income, awareness of the evacuation center and knowledge on the proximity of the evacuation center to the three predictors of the Theory of Planned Behavior; however, findings show nuances on the significance of socio-demographic determinants unique to locations in the provinces. Results revealed that the existing programs of the government on disaster management are focused more on buildingawareness that helped in building the intention to follow pre-emptive evacuation procedures. Risk communication strategies should be designed context specific.